La persistencia de la razón en la locura : Recuperación de la antigua imprenta del Borda - Ares, Fabio Eduardo (2018)
The printing house of the Hospicio de las Mercedes (now called Hospital José T. Borda) was opened with three aims: producing administrative materials, serving as a therapeutic workshop and spreading new ideas about the treatment of insanity through the publication of the newspaper Eco de las Mercedes. Since 2016 I have been working on an institutional study project and value of the heritage of this place. I address this project mainly from the observation of the technologies and printed documents found in the establishment and from the comparison between them and typographic samples, publications, printed documents and tools from other workshops and shops of that time.